2002
DOI: 10.4049/jimmunol.168.10.5170
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of a Unique Direct Prothrombinase, fgl2, and Identification of a Serine Residue Critical for the Prothrombinase Activity

Abstract: fgl2 prothrombinase, by its ability to generate thrombin, has been shown to be pivotal to the pathogenesis of viral-induced hepatitis, cytokine-induced fetal loss syndrome, and xeno- and allograft rejection. In this study, the molecular basis of fgl2 prothrombinase activity was examined in detail. Purified fgl2 protein generated in a baculovirus expression system had no measurable prothrombinase activity, whereas the activity was restored when the purified protein was reconstituted into phosphatidyl-l-serine-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 38 publications
2
70
0
Order By: Relevance
“…While studying a lethal coagulopathy induced by hepatitis virus in certain strains of mice, Levy and coworkers (5) identified Fgl2 as the target of a mAb that suppressed the coagulopathy. Follow-up in vitro studies suggested that Fgl2 possesses direct coagulant activity (8). Fgl2-specific antibodies were also found to suppress the coagulationassociated spontaneous abortion that characterizes certain mouse strain breeding combinations (6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While studying a lethal coagulopathy induced by hepatitis virus in certain strains of mice, Levy and coworkers (5) identified Fgl2 as the target of a mAb that suppressed the coagulopathy. Follow-up in vitro studies suggested that Fgl2 possesses direct coagulant activity (8). Fgl2-specific antibodies were also found to suppress the coagulationassociated spontaneous abortion that characterizes certain mouse strain breeding combinations (6).…”
Section: Discussionmentioning
confidence: 99%
“…Given that Fgl2 is IFN␥-inducible (Figs. 1 and 2) and putatively contributes to fibrin formation (5,7,8), we evaluated T. gondii infection in Fgl2-deficient mice. In contrast to IFN␥-or fibrin-deficient mice, which succumb within 2 weeks of infection (12,27), Fgl2-deficient mice survived acute infection by strain ME49 T. gondii.…”
Section: Fgl2mentioning
confidence: 99%
See 2 more Smart Citations
“…The prothrombinase fibroleukin (fibrinogen-like protein 2, FGL2) is related to the fibrinogen beta and gamma chains, which can directly cleave prothrombin to thrombin (Chan et al, 2002). FGL2 appears to exist in two forms: a membrane-linked FGL2 with prothrombinase activity, and a soluble FGL2 that has potent immunosuppressive activity .…”
Section: Activity Of Immune Response/inflammationrelated Genes Duringmentioning
confidence: 99%